Arrhythmogenic gene remodelling in elderly patients with type 2 diabetes with aortic stenosis and normal left ventricular ejection fraction. Issue 11 (24th September 2017) - Ashrafi, R.; Modi, P.; Oo, A. Y.; Pullan, D. M.; Jian, K.; Zhang, H.; Gerges, J. Yanni; Hart, G.; Boyett, M. R.; Davis, G. K.; Wilding, J. P. H.
Abstract : New Findings: What is the central question of this study? Type 2 diabetes is associated with a higher rate of ventricular arrhythmias compared with the non‐diabetic population, but the associated myocardial gene expression changes are unknown; furthermore, it is also unknown whether any changes are attributable to chronic hyperglycaemia or are a consequence of structural changes. What is the main finding and its importance? We found downregulation of left ventricular ERG gene expression and increased NCX1 gene expression in humans with type 2 diabetes compared with control patients with comparable left ventricular hypertrophy and possible myocardial fibrosis. This was associated with QT interval prolongation. Diabetes and associated chronic hyperglycaemia may therefore promote ventricular arrhythmogenesis independently of structural changes. Type 2 diabetes is associated with a higher rate of ventricular arrhythmias, and this is hypothesized to be independent of coronary artery disease or hypertension. To investigate further, we compared changes in left ventricular myocardial gene expression in type 2 diabetes patients with patients in a control group with left ventricular hypertrophy. Nine control patients and seven patients with type 2 diabetes with aortic stenosis undergoing aortic valve replacement had standard ECGs, signal‐averaged ECGs and echocardiograms before surgery. During surgery, a left ventricular biopsy was taken, and mRNA expressions for genes relevant to the cardiac action potential were estimated by RT‐PCR. Mathematical modelling of the action potential and calcium transient was undertaken using the O'Hara–Rudy model using scaled changes in gene expression. Echocardiography revealed similar values for left ventricular size, filling pressures and ejection fraction between groups. No difference was seen in positive signal‐averaged ECGs between groups, but the standard ECG demonstrated a prolonged QT interval in the diabetes group. Gene expression of KCNH2 and KCNJ3 were lower in the diabetes group, whereas KCNJ2, KCNJ5 and SLC8A1 expression were higher. Modelling suggested that these changes would lead to prolongation of the action potential duration with generation of early after‐depolarizations secondary to a reduction in density of the rapid delayed rectifier K + current and increased Na + –Ca 2+ exchange current. These data suggest that diabetes leads to pro‐arrythmogenic changes in myocardial gene expression independently of left ventricular hypertrophy or fibrosis in an elderly population. Abstract :